A study of sexual dysfunction in females having major depressive disorder - Surabhi Sharma (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2024)
Introduction: Major depressive disorder has the highest lifetime prevalence of any psychiatric disorder and negatively impacts sexual functioning in many patients. Females hesitate to discuss sexual problems due to cultural barriers. So sexual dysfunctions are under-reported and under-studied. Method: This is a cross-sectional study to evaluate the pattern of sexual dysfunction in 18 to 40-year-old married females having major depressive disorder attending psychiatry OPD in a tertiary care hospital in Delhi, India. The severity of depression was assessed by the Hamilton Depression Rating Scale (HAM-D), and sexual functioning was assessed by the Arizona Sexual Experience Scale (ASEX) and Female Sexual Function Index (FSFI) scales. Data was analysed using SPSS. Mean and standard deviation (±SD) were used to describe quantitative data meeting normal distribution. As appropriate, the chi-square or Fisher's exact test was used to compare categorical data amongst independent groups.  Results: 64% and 56% of participants in drug naïve and on-treatment groups respectively had sexual dysfunction as per ASEX scale as compared to 10% of controls. As per the FSFI scale, 84% and 76% of participants of drug naïve and on-treatment groups had sexual dysfunction compared to 20% of the control group. Of all domains of sexual functioning, domains of desire, arousal, and orgasm were most commonly affected.  Conclusion: This study showed a high prevalence of sexual dysfunction in depressed females emphasizing the need for direct inquiry about sexual problems by the treatment provider and appropriate management for the benefit of patients.